A framework for analyzing public reason theories - Billingham, P; Taylor, A (SAGE Publications, 2020)
Proponents of public reason views hold that the exercise of political power ought to be acceptable to all reasonable citizens. This paper elucidates the common structure shared by all public reason views, first by identifying a set of question that all such views must answer and, second, by showing that the answers to these questions stand in a particular relationship to each other. In particular, we show that what we call the ‘rationale question’ is fundamental. This fact, and the common structure more generally, is often overlooked or distorted within the literature. As a result, we argue, several prominent argumentative moves made by both critics and defenders of public reason are unsuccessful. Our overall conclusion is that discussions of public reason views would be more fruitful if they made consistent use of the common structure we identify.